2007
DOI: 10.1111/j.1537-2995.2007.01490.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function under high‐shear conditions from platelet concentrates

Abstract: BACKGROUND: Platelet (PLT) collection and storage affect the functional capacity of PLTs in PLT concentrates (PCs). Therefore, PLTs' functional quality should be studied before transfusion. STUDY DESIGN AND METHODS: PCs (n = 15) were collected by a standard apheresis procedure (Trima, Gambro BCT) and were stored for 7 days. Samples were taken to assess PLT adhesion and aggregate formation by a cone and plate analyzer (Impact-R, DiaMed) on Days 1, 3, 5, and 7 after harvesting. This device allows testing PLT fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
31
2
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 34 publications
6
31
2
2
Order By: Relevance
“…However, Cardigan et al (21) reported that the reactivity of platelets to stimuli such as physiological agonists, rather than the glycoprotein expression without agonists, might be a better predictor of in vivo platelet transfusion efficacy. Recently, several studies have reported on CD62P expression in agonist-stimulated platelets for the evaluation of platelet function in platelet products (8)(9)(10)(11)(12)(13)(14)(15). However, agonist-induced expression of CD62P by flow cytometry analysis is not easy to use routinely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Cardigan et al (21) reported that the reactivity of platelets to stimuli such as physiological agonists, rather than the glycoprotein expression without agonists, might be a better predictor of in vivo platelet transfusion efficacy. Recently, several studies have reported on CD62P expression in agonist-stimulated platelets for the evaluation of platelet function in platelet products (8)(9)(10)(11)(12)(13)(14)(15). However, agonist-induced expression of CD62P by flow cytometry analysis is not easy to use routinely.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, agonist-induced expression of CD62P, or other markers, has been investigated in several studies to determine platelet function in platelet products (8)(9)(10)(11)(12)(13)(14)(15), because the functional reactivity of platelets could be used to predict platelet transfusion efficacy. However, agonist-induced expression of CD62P by flow cytometry analysis has some disadvantages, including the expense of the equipment and reagents, and the difficulty of the associated procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The collagen beads did not change in percentage of beads with adhering platelets, but did increase the amount of platelets adhering to each bead during the first 7 days of storage. There are few studies on platelet adhesion during storage and they vary in the method of platelet preparation, storage length and storage media, making direct comparisons difficult, as all these factors affect platelet function [6,7,[9][10][11]. Furthermore these studies have tested platelets in presence of added red blood cells which could also influence their results.…”
Section: Discussionmentioning
confidence: 99%
“…One reason is that current available methods are time consuming, complicated to use, and require large sample volumes. The adhesion capacity of stored platelets has been studied using perfusion chambers [6][7][8] or cone and-plate devices [9,10]. These methods require the presence of red blood cells, which complicates the analysis of PCs and introduces a potential source of non-specific and unpredictable effects [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some drugs can irreversibly interfere in platelet function; these drugs include antimicrobial and anti-inflammatory drugs, and, in particular, cyclooxygenase inhibitors such as acetylsalicylic acid, which block the synthesis of thromboxane A2, a potent platelet aggregation activator. (20) In our study, the results of platelet aggregation in donor whole blood, both with ADP and collagen, were considered normal, showing that the blood collection process did not significantly affect platelet function and also that donors had not been taking drugs that had an effect on these cells.…”
Section: Discussionmentioning
confidence: 62%